Effectiveness of Online Oral Health Education During the Covid-19 Pandemic - Nila Kasuma1 , M. Biomed1 , Murniwati2 , Dedi Sumantri3 , Reni Nofika4 , Surya Nelis1 , Susi2, Aria (Indian Journal of Forensic Medicine & Toxicology, 2020)
This study aims at analyzing the effectiveness of online public education about oral health during theCOVID-19 pandemic. Studies show that humans touch their face 23 times in 1 hour and touch their mouthand its surroundings 4 times per hour with a duration of 1-12 seconds. This can cause the transmission ofthe virus through the oral, nasal, or conjunctival mucosa. How oral hygiene can contribute to reducing therisk of Corona Virus transmission between humans is the main focus of this study. Dental procedures carryhigh risk of exposure to Covid-19 through saliva, blood and other body fluids from patients, the use of highspeed instruments also increases the risk of infection in practice. The incubation period of 7-24 days exposesdentists and patients to cross-infection that can be transmitted through the oral cavity and respiratory tract.The study reveals that a great part of the population in Indonesia, especially in West is unaware of thetransmission of the Corona Virus through dental procedures. Consequently, the study suggests that onlineoral education is suitable for raising the community’s awareness of the Covid-19 pandemic.